Assessment of the Student Satisfaction on the Consultation Program - Montebon, Richie L.; Bachanicha, Rafael M. (JPAIR Institutional Research, 2018)
Understanding student satisfaction with the student services of the department can be useful for higher education institutions in identifying their strengths, and, as well as areas that could be improved. This study determined the customer satisfaction of the consultation program on the College of Hotel and Restaurant Management of University of Cebu-Lapu Lapu and Mandaue, Cebu City, Philippines. This study utilized the descriptive method and weighted mean for summarizing data and used a researcher-made questionnaire. Respondents who had been referred to the program were randomly selected from all year levels. Findings revealed that the overall result on the customer satisfaction was satisfactory. It shows that the consultation program is effective in guiding students who have academic and personal problems. This study also revealed that the faculty as a counselor display willingness in accommodating the students and helpful in giving them advice. It is evident that the program contributed to the existence of the student in leading the right way and is solving problems. With this, the program should be continued so that the students will have a proper venue they can discuss and express their problems and concerns.